2018
DOI: 10.1055/s-0037-1612620
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Developmental Disorders in 4 to 60 Months Old Children in Iran (2015–2016)

Abstract: Developmental delay occurs when children fail to reach their developmental milestones at the appropriate time. The aim of this study was to determine the prevalence of developmental disorders as well as their correlations with selected demographic factors affecting development in children 4 to 60 months old in Khorramabad, Iran from 2015 to 2016. In this cross-sectional study, 500 children from 4 to 60 months of age and visiting health service centers were selected. Developmental status was measured using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is in alignment with a study done in Iran in 2017 on 500 children aged 4 to 60 months the prevalence of developmental delay was 8.5%. (11) While it is lower than the frequency found in a study conducted in multiple PHC centers in Saudi Arabia in 2020 done on 948 children 16.4%. (13) These differences could be attributed to differences in the screening tools used as well as the study setting.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This is in alignment with a study done in Iran in 2017 on 500 children aged 4 to 60 months the prevalence of developmental delay was 8.5%. (11) While it is lower than the frequency found in a study conducted in multiple PHC centers in Saudi Arabia in 2020 done on 948 children 16.4%. (13) These differences could be attributed to differences in the screening tools used as well as the study setting.…”
Section: Discussionmentioning
confidence: 75%
“…(14) However, in a study conducted by Ahmadipour in Iran the fine motor domain revealed the largest number of delayed children. (11) These differences could be attributed to difference in cultural factors. Some cultures believe motor development (like sitting and walking) is the most important indicator of a child's health thus focusing on helping their children develop these skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations